The Influence of Financial Management and Financial Inclusion through HR Competence on MSME Performance - Muhammad Fadhlan Muflih (Scientia Integritas Utama, 2023)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy because of their contribution to economic growth and job creation. However, MSMEs often face challenges in managing finances and accessing formal financial services, which can affect their business performance. This study aims to identify the influence of financial management and financial inclusion through the competence of Human Resources (HR) on the performance of MSMEs in Makassar City . The research method used is a survey by collecting data from 100 respondents of MSME owners or managers in Makassar city . The variables studied included financial management, financial inclusion, HR competence, and MSME performance. Data were analyzed using Path Analysis. The results of the study show that financial management and financial inclusion have a significant effect on performance MSMEs. MSMEs that have good financial management and wider access to formal financial services tend to have better business performance. In addition, HR competencies also have a positive influence on MSME performance. Competent human resources are able to manage finances efficiently, make smart decisions, and innovate in increasing business competitiveness.